PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN HASIL BELAJAR MATERI PECAHAN SISWA KELAS II - Adela Larissa Amanda Polii; Juliana Margareta Sumilat; Gracia Gabriella Gampu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine the implementation of the Project Based Learning model to improve learning outcomes on fraction material among Grade II students of SD Inpres Kolongan Atas Sonder. The method used was Classroom Action Research, consisting of planning, action, observation, and reflection stages. Prior to the intervention, students’ learning completeness was very low. After the implementation of the Project Based Learning model, learning outcomes improved significantly. The model also fostered 21st-century skills 4C, students demonstrated critical thinking when determining how to divide an object into equal parts, creativity in designing and coloring the “Fraction Pizza Painting” media, collaboration while working in groups, and communication when presenting their project results. This is evidenced by a learning achievement rate of 83.3% with an average score of 80.96. It can be concluded that the Project Based Learning model is effective in improving learning outcomes on fraction material among Grade II students at SD Inpres Kolongan Atas Sonder.